2009
DOI: 10.1021/ol802844z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amidines Using N-Allyl Ynamides. A Palladium-Catalyzed Allyl Transfer through an Ynamido−π-Allyl Complex

Abstract: A de novo transformation of N-allyl-N-sulfonyl ynamides to amidines is described featuring a palladium-catalyzed N-to-C allyl transfer via ynamido-palladium-π-allyl complexes.Our involvement in the studies of Huisgen's azide-[3 + 2] 1-3 cycloadditions employing ynamides 4-7 led us to an exciting possibility. As shown in Scheme 1, under copper(I)-catalyzed conditions, 8 while triazolyl copper intermediates 1 could be trapped with electrophiles other than proton to afford more substituted triazoles 2 ,9,10 when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 68 publications
0
37
0
1
Order By: Relevance
“…Hsung142 recently disclosed a thermal aza -Claisen rearrangement of silylated ynamides 555 to isolable ketenimines 556 , which can be trapped in situ with nucleophilic amines (Scheme 147). In refluxing toluene, the reaction proceeded efficiently to give allylated amidines 557 in high yields as a complementary method to the palladium-catalyzed reaction (Section 3.7).…”
Section: Reactions Of Ynamidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsung142 recently disclosed a thermal aza -Claisen rearrangement of silylated ynamides 555 to isolable ketenimines 556 , which can be trapped in situ with nucleophilic amines (Scheme 147). In refluxing toluene, the reaction proceeded efficiently to give allylated amidines 557 in high yields as a complementary method to the palladium-catalyzed reaction (Section 3.7).…”
Section: Reactions Of Ynamidesmentioning
confidence: 99%
“…Hsung and Zhang142 recently reported a possible metallo-ynamido complex in their work on the synthesis of amidines 668 from N -allyl ynamides 665 (Scheme 167). Pd(0) was found to catalyze an N -to- C allyl transfer presumably through oxidative addition into the C — N bond to form an ynamido-Pd-π-allyl complex in equilibrium with the ketenimine-Pd complex 666 .…”
Section: Reactions Of Ynamidesmentioning
confidence: 99%
“…It was also adapted to prepare N -substituted amidines 25 related to earlier derivatives. 26 However, for BI and azaBI systems, LHMDS deprotonates the ring NH, preventing the desired reaction due to a delocalized negative charge on the nitrile. Thus, amidines of such systems are usually prepared by one of the other two methods.…”
mentioning
confidence: 99%
“…4 Most notably, it was demonstrated that N -phosphoryl- N -allyl ynamides 1 [for EWG = PO(OR) 2 ] could undergo a thermal 3- aza -Claisen rearrangement 5,6 to generate allyl ketenimine 7 intermediates 2 in situ without suffering a subsequent facile 1,3-shift observed in related N -sulfonyl systems [ 1 ➡ 4 when EWG = ArSO 2 ], leading to an effective formation of structurally unique quaternary nitriles 5 8,9 (Scheme 1). While such a 1,3-sulfonyl shift can be of immense interest, 10 it precluded us from developing a useful carbocyclization of allyl ketenimines 4 .…”
mentioning
confidence: 99%